The Correlation Between Informal Peer Communication in English and Students’ Self-Confidence in Speaking English in Class at MAS Pondok Pesantren Syafa'aturrasul - Desi Lestari; Prih Febtiningsih; Qonaah Nuryan Arif (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to determine the relationship between informal peer communication in English and students’ self-confidence in speaking English in class among twelfth-grade students of MAS Pondok Pesantren Syafa’aturrasul. The research employed a quantitative approach with a correlational design. The sample consisted of all 64 twelfth-grade students selected using a total sampling technique. Data were collected through questionnaires on informal peer communication and self-confidence in speaking English. Data analysis was carried out using SPSS 26 with normality, linearity, and Pearson Product-Moment correlation tests. The results showed a strong and significant positive relationship between informal peer communication in English and students’ self-confidence in speaking English in class (r = 0.690; p < 0.05). This indicates that the more frequently students engage in informal communication in English with their peers, the higher their self-confidence in speaking English in class. The study highlights the importance of peer interaction in enhancing students’ confidence and encourages teachers to create a supportive environment that fosters English communication practice among students.